2017
DOI: 10.3390/su9091567
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Transformational Leadership on Employee Sustainable Performance: The Mediating Role of Organizational Citizenship Behavior

Abstract: Abstract:Transformational leadership has drawn extensive attention in management research. In this field, the influence of transformational leadership on employee performance is an important branch. Recent research indicates that organizational citizenship behavior plays a mediating role between transformational leadership and employee performance. However, some of these findings contradict each other. Given the background where greater attention is being paid to transformational leadership in the construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
157
1
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(223 citation statements)
references
References 70 publications
17
157
1
15
Order By: Relevance
“…Furthermore, TL increases the intellectual ability of employees (Fletcher et al, 2019). Past research shows that several of the world's most successful companies have achieved their goals by implementing the TL process (Sow et al, 2016;Dedaj, 2017;Jiang et al, 2017;Maaitah, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TL increases the intellectual ability of employees (Fletcher et al, 2019). Past research shows that several of the world's most successful companies have achieved their goals by implementing the TL process (Sow et al, 2016;Dedaj, 2017;Jiang et al, 2017;Maaitah, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The transformational leader motivates the employees to strive for the collective goals, and stimulating followers' focus and understanding towards the organizational vision [32]. For example, Bass and Riggio [33] suggested that transformational leadership enhances the creative effort in an organization and contributes to the innovative goal.…”
Section: Main Effects: Leadership Styles and Project-based Organizatimentioning
confidence: 99%
“…Ricard et al found that public leadership is influenced by transformational leadership to a great extent. Other research has shown that sustainable employee performance is positively influenced by transformational leadership (Jiang, Zhao, & Ni, ). Furthermore, Nikezić, Doljanica, and Bataveljić () observed that charismatic and transformational leadership affects individuals and their culture with transformational leadership having more of an impact than charismatic leadership.…”
Section: Introductionmentioning
confidence: 93%